Episódios históricos no contexto do Ensino de Ciências: A energia nuclear e sua utilização - Andrade Júnior, José Adauto (2015)
It is notorious and almost unquestionable close relationship between the sciences and society. A historical example was the high investment that the U.S. did in their primary schools during the Cold War. Aiming their students promoted the greatest technological advances in a short time, Americans challenged by the former Soviet Union, they induced a revolution in basic science teaching with new projects and major investments that, in fact, boosted the technological advancement of the country. Just before, during the Second World War, there is also a large handling in the sciences laboratories hampered through external social demands, especially those related to the production of nuclear energy. In order to provide to the learner skills of understanding reality, participation, and critical awareness, this work developed under the approach Science-Technology-Society aims to describe and discuss the concept of students basic education about nuclear energy and its use from using historical episodes. Two historical episodes that marked the beginning of the age of nuclear energy will be work: the Manhattan Project and the launch of the bombs on Hiroshima and Nagasaki. These events were chosen from the assumption that they were the most responsible in communicating to the world about the risks of this form of energy. Based on these episodes, discussions will be promote in the classroom, providing students with cognitive skills and reasoning and researcher teacher a wide research material.